Implementing Character Education in Madrasah - Syarnubi, Syarnubi; Mansir, Firman; Purnomo, Mulyadi Eko; Harto, Kasinyo; Hawi, Akmal (Jurnal Pendidikan Islam, 2021)
This study investigated the application model of character education in Islamic Religious Education learning and spiritual extracurricular activities in Madrasah Aliyah Negeri 3 Palembang. Data were collected using participatory observation, in-depth interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusions. The results show that the implementation model of character education is a collaboration between the integration model and the supplement. Character education is collaborated through learning Islamic Religious Education and spiritual extracurricular activities. These two activities produce knowledge, attitudes, and moral actions on the part of students. The success of character education can be seen from the behavior of students who have religious behavior, honest, disciplined, responsible, caring, polite, cooperative, creative, hard-working, curious, friendly, and social care. There were some factors that supported the success of character education and they include religious programs, dormitories, and facilities. Meanwhile, the inhibiting factors for the success of character education were the negative influence of technology, limited supervision by madrasa institutions, and weak cooperation between madrasas and parents of students.